Unexpected, unforeseen, unplanned: Scenarios of international foreign and security policy. Foresight Contributions 2015 - Lars Brozus (Stiftung Wissenschaft und Politik (SWP), 2016)
There is little politicians and administrations fear more than being taken off guard and ill-prepared by a major incident. However inadequate the planning and instruments, decisions must be made and action taken. As such, unexpected events expose decision-makers to the risks of portentous decisions arrived at under conditions of great uncertainty, and usually also in great haste. Space for reflection, analysis and consultation is scarce. The problem is heightened in the sphere of foreign and security policy, with its multitude of actors, interests and influences: here, the unexpected is to be expected (see SWP Foresight Studies from 2011 and 2013). Revolutionary upheavals and power struggles frequently obliterate the bounds of orderly political process. Recent examples include developments in the Middle East and North Africa since 2011 and Russia's response to the toppling of the government in Ukraine in early 2014. Retrospective analyses of unexpected events often reveal that there were in fact warning signs. Indeed, these are generally even recognised in good time - but not interpreted as they would have in light of their later relevance. Therefore, the authors of the third SWP Foresight Study discuss possible future scenarios that already deserve more political attention today. The common starting point for all contributions is that the outlined situation would present German (and EU) foreign and security policy with grave challenges, regardless of whether the character of the events is more of a crisis or an opportunity. (SWP Research Paper)
Keywords: 320